Early rehabilitation after stroke. Issue 1 (February 2017) - Bernhardt, Julie; Godecke, Erin; Johnson, Liam; Langhorne, Peter
Abstract : Purpose of review: Early rehabilitation is recommended in many guidelines, with limited evidence to guide practice. Brain neurobiology suggests that early training, at the right dose, will aid recovery. In this review, we highlight recent trials of early mobilization, aphasia, dysphagia and upper limb treatment in which intervention is commenced within 7 days of stroke and discuss future research directions. Recent findings: Trials in this early time window are few. Although the seminal AVERT trial suggests that a cautious approach is necessary immediately (<24 h) after stroke, early mobility training and mobilization appear well tolerated, with few reasons to delay initiating some rehabilitation within the first week. The results of large clinical trials of early aphasia therapy are on the horizon, and examples of targeted upper limb treatments with better patient selection are emerging. Summary: Early rehabilitation trials are complex, particularly those that intervene across acute and rehabilitation care settings, but these trials are important if we are to optimize recovery potential in the critical window for repair. Concerted efforts to standardize 'early' recruitment, appropriately stratify participants and implement longer term follow-up is needed. Trial standards are improving. New recommendations from a recent Stroke Recovery and Rehabilitation Roundtable will help drive new research.